Laminate for anti-reflection film, anti-reflection film, and method for producing laminate for anti-reflection film
The laminate structure with a base film, optical interference, and uncured hard coat layers addresses the issues of thermoformability and scratch resistance in antireflection films, providing enhanced performance in various applications.
Patent Information
- Application Number
- JP2021507389
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-18
- Filing Date
- 2020-03-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-03-18
AI Technical Summary
Conventional antireflection films lack sufficient thermoformability and scratch resistance, which limits their applicability and durability in various applications.
A laminate structure is developed comprising a base film with a release surface, an optical interference layer, and an uncured hard coat layer, where the optical interference and uncured hard coat layers are laminated in contact, and optionally include an adhesive layer, with specific refractive index ranges and thicknesses to enhance antireflection properties, thermoformability, and scratch resistance.
The laminate structure achieves high antireflection properties, excellent thermoformability, and improved scratch resistance, enabling its use in diverse applications such as computer screens, television screens, and electronic device housings.
Smart Images

Figure 0007600981000020 
Figure 0007600981000021 
Figure 0007600981000022
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate for an antireflection film suitable for producing an antireflection film, and in particular to a laminate for an antireflection film in which an optical interference layer such as a low refractive index layer and an uncured hard coat layer are laminated so as to be in contact with each other. [Background technology]
[0002] Conventionally, laminated films that have a surface with low reflectance and can be used as anti-reflection films are known (see Patent Document 1). Laminated films with low surface reflectance are used in applications such as computer screens, television screens, plasma display panels, the surfaces of polarizing plates used in liquid crystal display devices, sunglasses lenses, prescription eyeglass lenses, camera viewfinder lenses, various instrument covers, automobile glass, train glass, in-vehicle display panels, and electronic device housings. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-41244 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0004] In the above-mentioned applications, many of the laminated films that have been conventionally used as anti-reflection films do not have sufficient thermoformability and are not necessarily good in abrasion resistance.
[0005] Therefore, an object of the present invention is to provide a laminate for an antireflection film, an antireflection film, etc. for producing an antireflection film having a low surface reflectance, good antireflection properties, and excellent thermoformability and scratch resistance. [Means for solving the problem]
[0006] Means for Solving the Problems The present inventors have conducted intensive research to solve the above-mentioned problems and have found that a laminate for an antireflection film, in which an optical interference layer such as a low refractive index layer and an uncured hard coat layer are laminated so as to be in contact with each other, is useful for producing an antireflection film having excellent antireflection properties as well as good thermoformability and scratch resistance, and have thus completed the present invention.
[0007] That is, the present invention is as follows. (1) a base film having a release surface; an optical interference layer laminated on the release surface; an uncured hard coat layer having a curable hard coat composition and laminated on the optical interference layer on the side opposite to the substrate film; a substrate layer having a thermoplastic resin and laminated on the uncured hard coat layer on the opposite side to the optical interference layer; A laminate for an anti-reflection film comprising: (2) The laminate for an antireflection film according to (1) above, wherein the optical interference layer and the uncured hard coat layer are pressure-bonded to each other so as to be in contact with each other. (3) The laminate for an antireflection film according to the above (1), further comprising an adhesive layer laminated between the optical interference layer and the uncured hard coat layer. (4) The laminate for an anti-reflection film according to the above (3), wherein the uncured hard coat layer comprises a curable, tack-free hard coat composition. (5) The laminate for an antireflection film according to any one of (1) to (4) above, wherein the refractive index of the base layer is 1.49 to 1.65, and the difference between the refractive index of the base layer and the refractive index of the uncured hard coat layer is in the range of 0.04 or less. (6) The laminate for an antireflection film according to any one of the above (1) to (5), wherein the optical interference layer has a low refractive index layer having a refractive index lower than that of the base layer or a high refractive index layer having a refractive index higher than that of the base layer. (7) The laminate for an antireflection film according to the above (6), wherein the refractive index of the base layer is from 1.49 to 1.65, and the refractive index of the low refractive index layer is from 1.31 to 1.41. (8) The laminate for an antireflection film according to the above (6) or (7), wherein the refractive index of the base layer is from 1.49 to 1.65, and the refractive index of the high refractive index layer is from 1.68 to 1.75. (9) The laminate for an antireflection film according to any one of the above (6) to (8), wherein the optical interference layer has the low refractive index layer and the high refractive index layer, and the high refractive index layer is laminated between the base layer and the low refractive index layer. (10) The laminate for an antireflection film according to any one of (6) to (8) above, wherein the optical interference layer has only one layer of the low refractive index layer, or one layer of the high refractive index layer and one layer of the low refractive index layer are laminated together. (11) The laminate for an antireflection film according to any one of the above (1) to (11), wherein the thickness of the base layer is 50 to 500 μm, and the thickness of the uncured hard coat layer is 1 to 10 μm. (12) The laminate for an antireflection film according to any one of the above (3) to (11), wherein the adhesive layer has a thickness of 1 to 10 μm. (13) The laminate for an antireflection film according to any one of the above (6) to (12), wherein the low refractive index layer has a thickness of 10 to 200 nm. (14) The laminate for an antireflection film according to any one of the above (6) to (13), wherein the high refractive index layer has a thickness of 10 to 300 nm. (15) The laminate for an antireflection film according to any one of (1) to (14) above, wherein the optical interference layer contains a polymer of a resin material containing a urethane acrylate and a (meth)acrylate. (16) The laminate for an antireflection film according to (15) above, wherein the resin material contains a fluorine-containing urethane acrylate. (17) The laminate for an antireflection film according to any one of (1) to (16) above, wherein the hard coat composition contains at least one of an acrylate monomer and an acrylate oligomer. (18) The laminate for an antireflection film according to (17) above, wherein the hard coat composition contains a urethane acrylate oligomer. (19) The laminate for an antireflection film according to any one of the above (3) to (18), wherein the adhesive layer contains an oligomer and / or polymer having a urethane bond, which is a reaction product between an oligomer and / or polymer of an acrylate compound having at least one hydroxy group and an isocyanate compound having at least one isocyanate group that bonds with the hydroxy group to form a urethane bond. (20) The laminate for an antireflection film according to (19) above, wherein the acrylate compound is an alkyl acrylate compound having 30 or less carbon atoms, and the isocyanate compound is an isocyanate compound having 20 or less carbon atoms and a methacryl group. (21) The laminate for an antireflection film according to (19) or (20) above, wherein the adhesive layer contains an oligomer and / or polymer having a urethane bond represented by the following formula (1): [ka] (In formula (1), n is an integer from 1 to 20.) (22) The laminate for an antireflection film according to any one of the above (1) to (21), wherein the optical interference layer is of an ultraviolet-curable type. (23) The laminate for antireflection films according to any one of the above (1) to (22), wherein when a sample of the laminate for antireflection films obtained by cutting into a size of 210 mm × 297 mm × 0.3 mm (thickness) is preheated at 190° C. for 40 seconds, the sample is placed in a mold including a right-angled protrusion having a deep-drawing height of 13 mm and a length and width of 30 mm so that the base layer is in contact with the sample of the laminate, and the sample of the laminate is subjected to pressure molding using high-pressure air of 1.5 MPa, the radius R of the region in contact with the right-angled portion of the mold obtained is 3.0 mm or less. (24) An antireflection film obtained by subjecting the laminate for an antireflection film according to any one of (1) to (23) above to thermoforming and ultraviolet curing. (25) An antireflection film having the laminate for an antireflection film according to any one of (1) to (23) above. (26) The antireflection film has a cured hard coat layer formed by curing the uncured hard coat layer, The antireflection film according to the above (24) or (25), wherein the refractive index of the base layer is 1.49 to 1.65, and the difference between the refractive index of the base layer and the refractive index of the cured hard coat layer is in the range of 0.04 or less. (27) The optical interference layer has a low refractive index layer having a refractive index lower than that of the base layer, The antireflection film according to any one of the above (24) to (26), wherein the refractive index of the base layer is from 1.49 to 1.65, and the refractive index of the low refractive index layer is from 1.31 to 1.41. (28) a first lamination step of laminating an optical interference layer on a release surface of a substrate film to form a first laminate; a second lamination step of laminating an uncured hard coat layer having a curable hard coat composition on one surface of the substrate layer containing a thermoplastic resin to form a second laminate; and a third lamination step of pressing the first and second laminates together so that the optical interference layer of the first laminate and the uncured hard coat layer of the second laminate are in contact with each other. (29) Laminating an optical interference layer on the release surface of a substrate film; a first lamination step of laminating an adhesive layer on a surface of the optical interference layer opposite to the release surface; a second lamination step of laminating an uncured hard coat layer having a curable, tack-free hard coat composition on one surface of the substrate layer containing a transparent resin to form a second laminate; and a third lamination step of pressing the first and second laminates together so that the adhesive layer of the first laminate and the uncured hard coat layer of the second laminate are in contact with each other. (30) The method for producing a laminate for an antireflection film according to (28) or (29) above, further comprising a first curing step of laminating a curable optical interference layer in the first lamination step and curing the optical interference layer between the first lamination step and the second lamination step. (31) The method for producing a laminate for an antireflection film according to any one of (28) to (30) above, further comprising a second curing step of curing the uncured hard coat layer after the third lamination step. (32) The method for producing a laminate for an antireflection film according to any one of the above (28) to (31), wherein the temperature during pressure bonding in the third lamination step is 20 to 100°C. (33) The method for producing a laminate for an antireflection film according to any one of (28) to (32) above, wherein in the third lamination step, the first and second laminates are pressure-bonded by applying a pressure of 4 MPa or less. Effect of the Invention
[0008] As described above, in the laminate for antireflection film of the present invention, an optical interference layer, for example a low refractive index layer, and an uncured hard coat layer are laminated so as to be in contact with each other. Such a laminate for antireflection film has superior moldability compared to a laminate having at least a cured hard coat layer, and is useful for producing an antireflection film with high antireflection properties. That is, the laminate for an antireflection film is subjected to, for example, molding or curing processes, or, if necessary, the base film laminated on the optical interference layer is removed to obtain an antireflection film. In this manner, the anti-reflection film produced from the laminate for an anti-reflection film contains an optical interference layer with an adjusted refractive index, and has excellent anti-reflection properties, as well as high thermoformability and scratch resistance.
[0009] Because of such excellent characteristics, the antireflection film of the present invention can be suitably used in applications such as display parts of computers, televisions, plasma displays, etc., surfaces of polarizing plates used in liquid crystal display devices, sunglasses lenses, prescription eyeglass lenses, camera viewfinder lenses, in-vehicle display panels, and housings for electronic devices. [Brief description of the drawings]
[0010] [Figure 1]FIG. 2 is a cross-sectional view showing a first laminate having a hard coat layer. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a second laminate having an optical interference layer. [Diagram 3] 3 is a cross-sectional view showing an example of a second laminate having an optical interference layer different from that shown in FIG. 2. FIG. [Figure 4] FIG. 4 is a cross-sectional view illustrating an outline of a lamination step in which two laminates are further laminated together. [Diagram 5] FIG. 13 is a diagram showing the elongation after pressure molding of an anti-reflection film having a surface on which lattice-like lines at predetermined intervals are printed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. Note that the present invention is not limited to the following embodiments, and can be modified and carried out as desired within the scope of the effects of the invention.
[0012] [1. Laminate for anti-reflection film] The laminate for an antireflection film has a substrate film, an optical interference layer, an uncured hard coat layer, and a substrate layer. The base film facilitates the formation of the optical interference layer and protects the optical interference layer by covering the surface of the optical interference layer after it is formed. The optical interference layer includes, for example, a low refractive index layer, and the optical characteristics of the optical interference layer are adjusted. Each layer constituting the optical interference layer has a refractive index value in a predetermined preferred range that is different from the refractive index value of the base layer. Although the hard coat layer is mainly formed of a curable material, it is not cured in the laminate for an antireflection film.
[0013] In one preferred embodiment of the laminate for anti-reflection films, the optical interference layer and the uncured hard coat layer are laminated so as to be in contact with each other, and in another preferred embodiment of the laminate for anti-reflection films, an adhesive layer is laminated between the optical interference layer and the uncured hard coat layer.
[0014] In this manner, the laminate for an antireflection film in which the above-mentioned layers are laminated is subjected to a process such as thermoforming or ultraviolet curing to cure the uncured hard coat layer, and further, if necessary, the substrate film, which will eventually become unnecessary, is peeled off from the optical interference layer to obtain an antireflection film. Hereinafter, each layer member included in the laminate for an anti-reflection film will be described.
[0015] <Base film> The laminate for an anti-reflection film includes a substrate film. The substrate film preferably has at least one release surface. The release surface is a surface of the substrate film that contacts the optical interference layer, which will be described in detail later, and is peelable from the optical interference layer. That is, in the laminate for antireflection film, the substrate film and the optical interference layer are maintained in a laminated state, but the substrate film that is no longer needed is peeled off from the laminate.
[0016] Although the substrate film facilitates the formation of the optical interference layer as described in detail below and protects the formed optical interference layer, the substrate film is not essential for the antireflection film as a final product, and therefore the substrate film is peeled off and removed from the optical interference layer at an appropriate time as necessary. In order to provide a release surface on the base film, for example, a release layer may be laminated on a resin substrate. In a base film having a release layer, the outer surface of the release layer functions as the release surface.
[0017] As the material for the base film, general-purpose resin films such as polyethylene terephthalate, polyethylene, polystyrene, polymethylpentene, polypropylene, etc. are used. A release agent is applied to the surface of such a substrate, for example made of resin, and then dried to form a base film having a release surface or layer. Examples of the method for forming a base film using a release agent include coating of a silicone-based release agent, coating of a long-chain alkyl-based release agent, coating of a fluorine-based release agent, etc. In addition, a single-layer substrate film made only of a release agent may be used without using a substrate such as a thermoplastic resin, etc. Specific examples of the substrate film include a release surface-containing PET film (release PET film), polyester, polyolefin, polystyrene, etc.
[0018] The thickness of the substrate film is not particularly limited, but is preferably 10 to 200 μm, and more preferably 25 to 50 μm.
[0019] <Optical interference layer> The optical interference layer included in the laminate for antireflection film has an antireflection function and includes at least one of a low refractive index layer and a high refractive index layer. The optical interference layer preferably includes at least a low refractive index layer.
[0020] The optical interference layer is preferably formed from a material having a curing property, for example, an ultraviolet curing type or a heat curing type. In addition, the optical interference layer included in the laminate for antireflection film is preferably subjected to a curing treatment. That is, the optical interference layer constituting one layer or two or more layers of the laminate for antireflection film is preferably cured.
[0021] (Low refractive index layer) The optical interference layer preferably has a single or multiple low refractive index layers, i.e., the optical interference layer may have only one low refractive index layer or may have multiple low refractive index layers. The low refractive index layer has a refractive index lower than that of the substrate layer, which will be described in detail later. The low refractive index layer suppresses reflection in the antireflection film obtained from the laminate for antireflection film. For this reason, the low refractive index layer is preferably disposed on the outermost side of the antireflection film, and therefore, in the laminate for antireflection film, the low refractive index layer is preferably disposed on the inner side of the substrate film so as to be in contact with the substrate film disposed on the outermost side.
[0022] The low refractive index layer preferably contains a polymer of a first resin material containing a fluorine-containing urethane acrylate and a (meth)acrylate, that is, the low refractive index layer is preferably formed by curing and polymerizing a resin material containing at least a fluorine-containing urethane acrylate and a (meth)acrylate.
[0023] Fluorine-containing urethane acrylate The fluorine-containing urethane acrylate contained in the first resin material of the low refractive index layer preferably contains at least a component represented by the following formula (2). (A3)-O(OC)HN-A2-HN(OC)-O-A1-O-(CO)NH-A2-NH-(CO)O-(A3)...(2) In the above formula (2), A1 may have a substituent and is preferably an alkylene group derived from a fluorine-containing diol having a total carbon number of 8 or less, and the total carbon number is preferably 6 or less, for example, 4. Examples of the substituent contained in the alkylene group of A1 include an alkyl group and the like.
[0024] In the above formula (2), A2 are each independently an alkylene group derived from an aliphatic or alicyclic isocyanate having a total of 4 to 20 carbon atoms, which may have a substituent. The number of carbon atoms in A2 is preferably 6 to 16, and more preferably 8 to 12. Examples of the substituent of the alkylene group in A2 include an alkyl group. As the alicyclic isocyanate forming A2, for example, isophorone diisocyanate of the following formula is used. [ka]
[0025] In the above formula (2), A3 each independently represents an alkyl group having a total of 4 to 30 carbon atoms, which contains at least one (meth)acryloyloxy group and may have a substituent. The total carbon number of A2 is preferably 6 to 20, more preferably 8 to 16. Examples of the substituent of the alkyl group of A3 include branched alkyl groups. A3 preferably contains at least two (meth)acryloyloxy groups, for example, three (meth)acryloyloxy groups. As a compound that forms A3, for example, pentaerythritol triacrylate of the following formula is used. [ka]
[0026] The fluorine-containing urethane acrylate is formed from each of the above-mentioned compounds and includes, for example, a compound represented by the following formula (3). [ka]
[0027] As described above, it is preferable to use fluorine-containing urethane acrylate as the material monomer of the low refractive index layer, but this is not limited thereto. For example, the low refractive index layer may be formed mainly from a polymer of urethane acrylate and a low refractive index member described later. As described above, the urethane acrylate polymer that can be used in combination with the low refractive index member is preferably a urethane acrylate containing a cyclic skeleton, more specifically, a polymer of an isocyanate compound and an acrylate compound, or a polymer of an isocyanate compound, an acrylate compound, and a polyol compound represented by the following formula:
[0028] Examples of the isocyanate compound include dicyclohexylmethane diisocyanate (H12MDI), isophorone diisocyanate (IPDI), and xylylene diisocyanate (XDI), which are represented by the following formula. [ka]
[0029] Examples of the acrylate compound include pentaerythritol triacrylate (PETA) and hydroxypropyl (meth)acrylate (hydroxypropyl acrylate: HPA), which are represented by the following formula. [ka]
[0030] An example of the polyol compound is tricyclodidecanedimethanol (TCDDM) represented by the following formula. [ka]
[0031] Specific preferred examples of the above-mentioned urethane acrylate polymer include a polymer of dicyclohexylmethane diisocyanate (H12MDI) and pentaerythritol triacrylate (PETA), a polymer of isophorone diisocyanate (IPDI) and PETA, a polymer of tricyclodidecanedimethanol (TCDDM), IPDI and PETA, a polymer of TCDDM, H12MDI and PETA, a polymer of xylylene diisocyanate (XDI) and hydroxypropyl (meth)acrylate (HPA), and the like.
[0032] The first resin material is (meth)acrylate. The (meth)acrylate contained in the first resin material of the low refractive index layer preferably contains at least one (meth)acryloyloxy group and at least one vinyl ether group, and is a compound having 4 to 20 carbon atoms which may have a substituent. The number of carbon atoms in the (meth)acrylate is preferably 6 to 18, and more preferably 8 to 16. Examples of the substituent in the (meth)acrylate include an alkyl group. As the (meth)acrylate, for example, 2-(2-vinyloxyethoxy)ethyl (meth)acrylate (VEEA) of the following formula is used. [ka] (In the above formula, R is hydrogen or a methyl group.)
[0033] In the first resin material, the ratio of the fluorine-containing urethane acrylate to the (meth)acrylate is preferably 99:1 to 30:70 (weight ratio), more preferably 97:3 to 60:40, even more preferably 95:5 to 80:20, and particularly preferably 90:10 to 50:50.
[0034] - Refractive index value of low refractive index layer The refractive index of the low refractive index layer is lower than that of the base layer, and is preferably about 1.31 to 1.41, more preferably about 1.32 to 1.39, and even more preferably about 1.33 to 1.38. The difference between the refractive index of the low refractive index layer and that of the substrate layer is preferably at least 0.09, more preferably at least 0.12, even more preferably at least 0.15, and particularly preferably at least 0.17. In this way, by increasing the difference between the refractive index of the low refractive index layer and that of the substrate layer, the reflectance of the surface on the low refractive index layer side of the antireflection film obtained from the laminate for antireflection film can be increased.
[0035] Low refractive index materials The low refractive index layer preferably includes a low refractive index member. The low refractive index member is added to reduce the refractive index of the low refractive index layer. That is, by forming the low refractive index layer using the low refractive index member, the difference in refractive index between the low refractive index layer and the substrate layer can be increased, and the reflectance of the anti-reflection film can be further reduced. As the low refractive index member, silica, metal fluoride fine particles, etc. are preferable, and silica, particularly hollow silica, is more preferable. In addition, when metal fluoride fine particles are used, examples of the metal fluoride contained in the particles include magnesium fluoride, aluminum fluoride, calcium fluoride, and lithium fluoride. The low refractive index member is preferably a particulate member, and the particle size (diameter) of the particulate low refractive index member is not particularly limited, but is, for example, 10 to 200 nm, preferably 30 to 100 nm, more preferably 35 to 80 nm, and particularly preferably 45 to 65 nm.
[0036] Other Ingredients The low refractive index layer or the first resin material forming the low refractive index layer preferably contains at least one of a photoinitiator (photopolymerization initiator) and a leveling agent, and more preferably contains a photoinitiator. In addition, the first resin material may contain a solvent. Examples of the leveling agent include a fluorine-based leveling agent and a silicone-based leveling agent.
[0037] The low refractive index layer preferably contains the first resin material and the low refractive index member in a weight ratio of 20:80 to 70:30, and the ratio of the first resin material to the low refractive index member is more preferably 30:70 to 65:35, and even more preferably 35:65 to 60:40.
[0038] The thickness of the low refractive index layer is not particularly limited, but is preferably 10 to 200 nm, more preferably 30 to 160 nm, further preferably 50 to 120 nm, and particularly preferably 80 to 110 nm.
[0039] (High refractive index layer) The optical interference layer preferably has a high refractive index layer. More preferably, the optical interference layer has a high refractive index layer in addition to the low refractive index layer. For example, in the optical interference layer, one high refractive index layer and one low refractive index layer are laminated. Also, for example, the optical interference layer has a high refractive index layer laminated directly so as to be in contact with the low refractive index layer. The high refractive index layer has a refractive index higher than the refractive index of the base layer, and has an anti-reflection function similar to the low refractive index layer.
[0040] The high refractive index layer preferably contains a polymer of a second resin material containing a urethane (meth)acrylate derived from a fluorene diol, an isocyanate, and a (meth)acrylate, and a (meth)acrylate. That is, the high refractive index layer is preferably a mixture of a urethane (meth)acrylate obtained by a dehydration condensation reaction of three components, a fluorene diol, an isocyanate, and a (meth)acrylate, and a (meth)acrylate.
[0041] ·Urethane (meth)acrylate The urethane (meth)acrylate contained in the second resin material of the high refractive index layer preferably contains at least a component represented by the following formula (4). (A3)-O(OC)HN-A2-HN(OC)-O-A1-O-(CO)NH-A2-NH-(CO)O-(A3) ···(4) (In formula (4), A1 is a structural unit derived from a fluorene diol, Each A2 is independently a structural unit derived from an isocyanate which may have a substituent, Each A3 is independently an alkyl group having a total of 4 to 30 carbon atoms, which contains at least one (meth)acryloyloxy group and may have a substituent such as an aryl group, the number of (meth)acryloyloxy groups being preferably 1 to 3, and the total number of carbon atoms being preferably 8 to 24.
[0042] Fluorene diol (A1) Representative examples of the fluorene-based diol for forming the above-mentioned structural unit A1, i.e., a compound having a fluorene skeleton, include the following. In this specification, the fluorene-based diol includes a fluorene compound having three or more hydroxyl groups. That is, examples of fluorene-based diols having two hydroxyl groups include 9,9-bis(hydroxyphenyl)fluorenes, 9,9-bis(hydroxy(poly)alkoxyphenyl)fluorenes, 9,9-bis(hydroxynaphthyl)fluorenes, and 9,9-bis(hydroxy(poly)alkoxynaphthyl)fluorenes. Examples of fluorene-based diols having three or more hydroxyl groups include 9,9-bis(polyhydroxyphenyl)fluorenes, 9,9-bis[poly(hydroxy(poly)alkoxy)phenyl]fluorenes, 9,9-bis(polyhydroxynaphthyl)fluorenes, and 9,9-bis[poly(hydroxy(poly)alkoxy)naphthyl]fluorenes.
[0043] Examples of 9,9-bis(hydroxyphenyl)fluorenes include 9,9-bis(hydroxyphenyl)fluorene [9,9-bis(4-hydroxyphenyl)fluorene (bisphenolfluorene) and the like], 9,9-bis(hydroxyphenyl)fluorene having a substituent {for example, 9,9-bis(alkyl-hydroxyphenyl)fluorene [9,9-bis(4-hydroxy-3-methylphenyl)fluorene (biscresolfluorene), 9,9-bis(4-hydroxy-3-ethylphenyl)fluorene, 9,9-bis(4-hydroxy-3-butylphenyl)fluorene, 9,9-bis(3-hydroxy-2-methylphenyl)fluorene, 9,9-bis(4-hydroxy-3,5-dimethylphenyl)fluorene, 9,9-bis(4-hydroxy-2,6-dimethylphenyl)fluorene and the like. 9,9-bis(mono- or di-C1-4 alkyl-hydroxyphenyl)fluorene, etc.], 9,9-bis(cycloalkyl-hydroxyphenyl)fluorene [9,9-bis(mono- or di-C5-8 cycloalkyl-hydroxyphenyl)fluorene such as 9,9-bis(4-hydroxy-3-cyclohexylphenyl)fluorene, etc.], 9,9-bis(aryl-hydroxyphenyl)fluorene [for example, 9,9-bis(mono- or di-C6-8 aryl-hydroxyphenyl)fluorene such as 9,9-bis(4-hydroxy-3-phenylphenyl)fluorene, etc.], 9,9-bis(aralkyl-hydroxyphenyl)fluorene [for example, 9,9-bis(C6-8 aryl-C1-2 alkyl-hydroxyphenyl)fluorene such as 9,9-bis(4-hydroxy-3-benzylphenyl)fluorene, etc.], etc.].
[0044] Examples of the 9,9-bis(hydroxy(poly)alkoxyphenyl)fluorenes include 9,9-bis(hydroxyalkoxyphenyl)fluorene {e.g., 9,9-bis(hydroxyC2-4alkoxyphenyl)fluorenes such as 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-hydroxypropoxy)phenyl]fluorene, 9,9-bis[4-(3-hydroxypropoxy)phenyl]fluorene, and 9,9-bis[4-(4-hydroxybutoxy)phenyl]fluorene, etc.}, 9,9-bis(hydroxyalkoxy-alkylphenyl)fluorene {e.g., 9,9-bis[4-(2-hydroxyethoxy)-3-methylphenyl]fluorene [or 2,2'-dimethyl-4,4'-(9-fluorenylidene)-bisphenoxyethanol], 9,9-bis[2-(2-hydroxyethoxy)-5-methylphenyl]fluorene, 9,9-bis[4-(2-hydroxyethoxy)-3-ethylphenyl]fluorene, 9,9-bis[4-(2-hydroxyethoxy)-3-propylphenyl]fluorene, 9,9 -Bis[4-(3-hydroxypropoxy)-3-methylphenyl]fluorene, 9,9-bis[4-(4-hydroxybutoxy)-3-methylphenyl]fluorene, 9,9-bis[4-(2-hydroxyethoxy)-3,5-dimethylphenyl]fluorene [or 2,2',6,6'-tetramethyl-4,4'-(9-fluorenylidene)-bisphenoxyethanol], 9,9-bis[4-(2-hydroxyethoxy)-3,5-diethylphenyl]fluorene, 9,9-bis[4-(3-hydroxypropoxy)-3,5-dimethylphenyl]fluorene phenyl]fluorene, 9,9-bis(hydroxy C2-4 alkoxy-mono or di C1-6 alkylphenyl)fluorenes such as 9,9-bis[4-(4-hydroxybutoxy)-3,5-dimethylphenyl]fluorene, etc.}, 9,9-bis(hydroxyalkoxy-cycloalkylphenyl)fluorene {for example, 9,9-bis(hydroxy C2-4 alkoxy-mono or di C5-8 cycloalkylphenyl)fluorenes such as 9,9-bis[4-(2-hydroxyethoxy)-3-cyclohexylphenyl]fluorene, etc.}, 9,9-bis(hydroxyalkoxy-arylphenyl)fluorenes {e.g., 9,9-bis[4-(2-hydroxyethoxy)-3-phenylphenyl]fluorene [or 2,2'-diphenyl-4,4'-(9-fluorenylidene)-bisphenoxyethanol], 9,9-bis[4-(2-hydroxyethoxy)-3,5-diphenylphenyl]fluorene, and other 9,9-bis(hydroxyC2-4 alkoxy-mono or diC6-8 arylphenyl)fluorenes}, 9,9-bis(hydroxyalkoxy-aralkylphenyl)fluorenes {e.g., 9,9-bis[4-(2-hydroxyethoxy)-3-benzylphenyl]fluorene, 9,9- 9,9-bis[hydroxyC2-4alkoxy-mono or di(C6-8arylC1-4alkyl)phenyl]fluorenes such as bis[4-(2-hydroxyethoxy)-3,5-dibenzylphenyl]fluorene} and 9,9-bis(hydroxyalkoxyphenyl)fluorenes corresponding to these 9,9-bis(hydroxyalkoxyphenyl)fluorenes, in which n is 2 or more in the formula (1) {for example, 9,9-bis[(hydroxyC2-4alkoxy)C2-4alkoxyphenyl]fluorene (compounds in which n=2) such as 9,9-bis{4-[2-(2-hydroxyethoxy)ethoxy]phenyl}fluorene} and the like} are included.
[0045] Examples of the 9,9-bis(hydroxynaphthyl)fluorenes include 9,9-bis(hydroxynaphthyl)fluorenes {e.g., 9,9-bis(monohydroxynaphthyl)fluorene which may have a substituent such as 9,9-bis[6-(2-hydroxynaphthyl)]fluorene (or 6,6-(9-fluorenylidene)-di(2-naphthol)), 9,9-bis[1-(6-hydroxynaphthyl)]fluorene (or 5,5-(9-fluorenylidene)-di(2-naphthol)), or 9,9-bis[1-(5-hydroxynaphthyl)]fluorene (or 5,5-(9-fluorenylidene)-di(1-naphthol))}.
[0046] Examples of the 9,9-bis(hydroxy(poly)alkoxynaphthyl)fluorenes include compounds corresponding to the 9,9-bis(hydroxynaphthyl)fluorenes, such as 9,9-bis(hydroxyalkoxynaphthyl)fluorene {e.g., 9,9-bis(hydroxyC2-4alkoxynaphthyl)fluorene which may have a substituent such as 9,9-bis[6-(2-(2-hydroxyethoxy)naphthyl)]fluorene, 9,9-bis[1-(6-(2-hydroxyethoxy)naphthyl)]fluorene [or 5,5'-(9-fluorenylidene)-bis(2-naphthyloxyethanol)], 9,9-bis[1-(5-(2-hydroxyethoxy)naphthyl)]fluorene, etc.}.
[0047] Examples of 9,9-bis(polyhydroxyphenyl)fluorenes include 9,9-bis(dihydroxyphenyl)fluorenes and 9,9-bis(trihydroxyphenyl)fluorenes. Examples of 9,9-bis(dihydroxyphenyl)fluorenes include 9,9-bis(dihydroxyphenyl)fluorene [9,9-bis(3,4-dihydroxyphenyl)fluorene (biscatechol fluorene), 9,9-bis(3,5-dihydroxyphenyl)fluorene, etc.], 9,9-bis(dihydroxyphenyl)fluorene having a substituent {for example, 9,9-bis(alkyl-dihydroxyphenyl)fluorene [9,9-bis(3,4-dihydroxy-5-methylphenyl)fluorene, 9,9-bis(3,4-dihydroxy-6-methylphenyl)fluorene, 9,9-bis(2,4-dihydroxy-3,6-dimethylphenyl)fluorene, etc.], 9,9-bis(mono- or di-C1-4 alkyl-dihydroxyphenyl)fluorenes such as 9,9-phenylphenyl)fluorene, 9,9-bis(aryl-dihydroxyphenyl)fluorene [for example, 9,9-bis(mono- or di-C6-8 aryl-dihydroxyphenyl)fluorenes such as 9,9-bis(3,4-dihydroxy-5-phenylphenyl)fluorene, and the like], 9,9-bis(alkoxy-dihydroxyphenyl)fluorene [for example, 9,9-bis(mono- or di-C1-4 alkoxy-dihydroxyphenyl)fluorenes such as 9,9-bis(3,4-dihydroxy-5-methoxyphenyl)fluorene], and the like] can be mentioned as examples.
[0048] Examples of 9,9-bis(trihydroxyphenyl)fluorenes include 9,9-bis(trihydroxyphenyl)fluorene [for example, 9,9-bis(2,4,6-trihydroxyphenyl)fluorene, 9,9-bis(2,4,5-trihydroxyphenyl)fluorene, 9,9-bis(3,4,5-trihydroxyphenyl)fluorene, etc.].
[0049] Examples of 9,9-bis[poly(hydroxy(poly)alkoxy)phenyl]fluorenes include 9,9-bis[di(hydroxy(poly)alkoxy)phenyl]fluorenes, 9,9-bis[tri(hydroxy(poly)alkoxy)phenyl]fluorenes, and the like.
[0050] Examples of 9,9-bis[di(hydroxy(poly)alkoxy)phenyl]fluorenes include 9,9-bis[di(hydroxyalkoxy)phenyl]fluorene {e.g., 9,9-bis[3,4-di(2-hydroxyethoxy)phenyl]fluorene [or 2,2'-bishydroxyethoxy-4,4'-(9-fluorenylidene)-bisphenoxyethanol], 9,9-bis[3,5-di(2-hydroxyethoxy)phenyl]fluorene [or 3,3'-bishydroxyethoxy-5,5'-(9-fluorenylidene)-bisphenoxyethanol], 9,9-bis[di(hydroxyC2-4alkoxy)phenyl]fluorene such as 9,9-bis[3,4-di(3-hydroxypropoxy)phenyl]fluorene, 9,9-bis[3,5-di(3-hydroxypropoxy)phenyl]fluorene, 9,9-bis[3,4-di(2-hydroxypropoxy)phenyl]fluorene, 9,9-bis[3,5-di(2-hydroxypropoxy)phenyl]fluorene, 9,9-bis[3,4-di(4-hydroxybutoxy)phenyl]fluorene, and 9,9-bis[3,5-di(4-hydroxybutoxy)phenyl]fluorene 9,9-bis[di(hydroxyalkoxy)phenyl]fluorene} having a substituent {for example, 9,9-bis[alkyl-di(hydroxyalkoxy)phenyl]fluorene [for example, 9,9-bis[mono or diC1-4 alkyl-di(hydroxyalkoxy)phenyl]fluorene such as 9,9-bis[3,4-di(2-hydroxyethoxy)-5-methylphenyl]fluorene, 9,9-bis[3,4-di(2-hydroxyethoxy)-6-methylphenyl]fluorene, and 9,9-bis[2,4-di(2-hydroxyethoxy)-3,6-dimethylphenyl]fluorene; 9,9-bis[aryl-di(hydroxyalkoxy)phenyl]fluorene, etc.], 9,9-bis[mono or diC6-8 aryl-di(hydroxyC2-4 alkoxy)phenyl]fluorene, etc., such as 9,9-bis[3,4-di(2-hydroxyethoxy)-5-arylphenyl]fluorene, etc.], 9,9-bis[alkoxy-di(hydroxyalkoxy)phenyl]fluorene, etc., such as 9,9-bis[3,4-di(2-hydroxyethoxy)-5-methoxyphenyl]fluorene, etc.9,9-bis[di(hydroxyalkoxy)phenyl]fluorenes such as 9-bis[mono or di C1-4 alkoxy-di(hydroxy C2-4 alkoxy)phenyl]fluorene]; 9,9-bis[di(hydroxypolyalkoxy)phenyl]fluorenes corresponding to these 9,9-bis[di(hydroxyalkoxy)phenyl]fluorenes, in which n is 2 or more in the formula (1) {for example, 9,9-bis[di(hydroxy C2-4 alkoxy C2-4 alkoxy]phenyl]fluorene (compounds with n = 2) such as 9,9-bis{3,4-di[2-(2-hydroxyethoxy)ethoxy]phenyl}fluorene and 9,9-bis{3,5-di[2-(2-hydroxyethoxy)ethoxy]phenyl}fluorene}, etc.}.
[0051] Examples of the 9,9-bis[tri(hydroxy(poly)alkoxy)phenyl]fluorenes include compounds corresponding to the 9,9-bis[di(hydroxy(poly)alkoxy)phenyl]fluorenes, such as 9,9-bis[tri(hydroxyalkoxy)phenyl]fluorene {e.g., 9,9-bis[2,3,4-tri(2-hydroxyethoxy)phenyl]fluorene [or 2,2',6,6'-tetrahydroxyethoxy-5,5'-(9-fluorenylidene)-bisphenoxyethanol], 9,9-bis[2,4,6-tri(2-hydroxyethoxy)phenyl]fluorene, 9,9-bis[2,4,5-tri(2-hydroxyethoxy)phenyl]fluorene, and 9,9-bis[3,4,5-tri(2-hydroxyethoxy)phenyl]fluorene. 9,9-bis[tri(hydroxyC2-4alkoxy)phenyl]fluorene}, and 9,9-bis[tri(hydroxypolyalkoxy)phenyl]fluorenes corresponding to these 9,9-bis[tri(hydroxyalkoxy)phenyl]fluorenes and having n of 2 or more in the formula (1) {for example, 9,9-bis[tri(hydroxyC2-4alkoxyC2-4alkoxy]phenyl]fluorenes (compounds where n = 2) such as 9,9-bis{2,4,6-tri[2-(2-hydroxyethoxy)ethoxy]phenyl}fluorene, 9,9-bis{2,4,5-tri[2-(2-hydroxyethoxy)ethoxy]phenyl}fluorene, and 9,9-bis{3,4,5-tri[2-(2-hydroxyethoxy)ethoxy]phenyl}fluorene}}.
[0052] The 9,9-bis(polyhydroxynaphthyl)fluorenes include compounds corresponding to the above-mentioned 9,9-bis(hydroxynaphthyl)fluorenes, for example, 9,9-bis(di- or trihydroxynaphthyl)fluorene.
[0053] In addition, the 9,9-bis[poly(hydroxy(poly)alkoxy)naphthyl]fluorenes include compounds corresponding to the 9,9-bis(hydroxy(poly)alkoxynaphthyl)fluorenes, for example, 9,9-bis[di- or tri(hydroxy(poly)alkoxy)naphthyl]fluorene and the like.
[0054] A preferred specific example of the above-mentioned fluorene-based diol is 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene.
[0055] Isocyanate (A2) The isocyanate for forming the structural unit A2 described above is not particularly limited, and examples thereof include aromatic, aliphatic, and alicyclic isocyanates.
[0056] For example, tolylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, tetramethylxylylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexa Examples of the polyisocyanate include polyisocyanates such as phenylene diisocyanate, lysine diisocyanate, lysine triisocyanate, and naphthalene diisocyanate, or trimer or tetramer compounds of these polyisocyanates, biuret-type polyisocyanates, water-dispersible polyisocyanates (for example, "Aquanate 100," "Aquanate 110," "Aquanate 200," and "Aquanate 210," manufactured by Nippon Polyurethane Industry Co., Ltd.), and reaction products of these polyisocyanates with polyols. Among these isocyanates, aromatic isocyanate compounds such as xylylene diisocyanate are preferred because they can easily achieve a high refractive index.
[0057] (Meth)acryloyloxy-containing alkyl group (A3) A preferred specific example of the component for forming the alkyl group of A3 above is a monofunctional (meth)acrylic compound having a hydroxyl group. Examples of the monofunctional (meth)acrylic compound having a hydroxyl group include hydroxyl group-containing mono(meth)acrylates {e.g., hydroxyalkyl(meth)acrylates [e.g., hydroxy C2-20 alkyl-(meth)acrylates such as 2-hydroxyethyl(meth)acrylate, 3-hydroxypropyl(meth)acrylate, and 6-hydroxyhexyl(meth)acrylate, preferably hydroxy C2-12 alkyl-(meth)acrylate, and more preferably hydroxy C2-6 alkyl-(meth)acrylate], polyalkylene glycol mono(meth)acrylates [e.g., poly C2-4 alkylene glycol mono(meth)acrylates such as diethylene glycol mono(meth)acrylate and polyethylene glycol mono(meth)acrylate], and hydroxyl groups having three or more hydroxyl groups. mono(meth)acrylates of polyols having the formula (e.g., alkane polyol mono(meth)acrylates such as glycerin mono(meth)acrylate and trimethylolpropane mono(meth)acrylate, and mono(meth)acrylates of polymers of alkane polyols such as diglycerin mono(meth)acrylate], N-hydroxyalkyl(meth)acrylamides (e.g., N-hydroxy C1-4 alkyl(meth)acrylamides such as N-methylol(meth)acrylamide and N-(2-hydroxyethyl)(meth)acrylamide), and adducts in which lactones (e.g., C4-10 lactones such as ε-caprolactone) are added to the hydroxyl groups of these compounds (e.g., hydroxyalkyl(meth)acrylates) (e.g., adducts in which about 1 to 5 moles of lactone are added). These (meth)acrylic compounds may be used alone or in combination of two or more kinds. A preferred specific example of the compound for forming the alkyl group (A3) containing a (meth)acryloyloxy group is 2-hydroxy-3-phenoxypropyl acrylate.
[0058] Preferable specific examples of the urethane (meth)acrylate contained in the second resin material include the following compounds. [ka] [ka] [ka] [ka]
[0059] The second resin material is (meth)acrylate. As the (meth)acrylate contained in the second resin material, i.e., the (meth)acrylate that is preferably used in combination with the above-mentioned urethane (meth)acrylate, the same type of compound as the (meth)acrylate contained in the first resin material can be adopted. The (meth)acrylate contained in the second resin material is preferably a compound containing at least one (meth)acryloyloxy group and at least one vinyl ether group, and having 4 to 20 carbon atoms which may have a substituent. The number of carbon atoms in the (meth)acrylate is preferably 6 to 18, and more preferably 8 to 16. Examples of the substituent in the (meth)acrylate include an alkyl group. As the (meth)acrylate, for example, 2-(2-vinyloxyethoxy)ethyl (meth)acrylate [2-(2-vinyloxyethoxy)ethyl acrylate: VEEA] is used.
[0060] A preferred example of the (meth)acrylate contained in the second resin material is a bisphenol A di(meth)acrylate compound having an ethoxy group. Preferred examples of the bisphenol A di(meth)acrylate compound having an ethoxy group include ethoxylated (3 mol) bisphenol A di(meth)acrylate, ethoxylated (4 mol) bisphenol A di(meth)acrylate, ethoxylated (10 mol) bisphenol A di(meth)acrylate, and propoxylated (3 mol) bisphenol A diacrylate, and a more preferred example is ethoxylated (4 mol) bisphenol A di(meth)acrylate.
[0061] In the second resin material, the ratio of urethane (meth)acrylate to (meth)acrylate is preferably 99:1 to 50:50 (weight ratio), more preferably 95:5 to 70:30, still more preferably 93:7 to 80:20, and particularly preferably 90:10 to 85:15.
[0062] The refractive index of the high refractive index layer is preferably from 1.68 to 1.75, more preferably from 1.69 to 1.74, and further preferably from about 1.70 to 1.73. The difference between the refractive index of the high refractive index layer and the refractive index of the substrate layer is preferably at least 0.09, more preferably at least 0.12, even more preferably at least 0.15, and particularly preferably at least 0.17. The difference between the refractive index of the high refractive index layer and the refractive index of the substrate layer is, for example, in the range of 0.03 to 0.70, preferably 0.10 to 0.50, and even more preferably 0.15 to 0.26. In this way, by increasing the difference between the refractive index of the high refractive index layer and the refractive index of the substrate layer, the reflectance of the surface on the optical interference layer side of the antireflection film obtained from the laminate for antireflection film can be further reduced.
[0063] <High refractive index materials> The high refractive index layer preferably contains a high refractive index member. The high refractive index member is added to increase the refractive index of the high refractive index layer. That is, by forming the high refractive index layer using the high refractive index member, the difference in refractive index between the high refractive index layer and the substrate layer can be increased, and the reflectance of the anti-reflection film can be further reduced. Examples of high refractive index members include titanium oxide, zirconium oxide (ZrO2), zinc oxide, alumina, colloidal alumina, lead titanate, red lead, yellow lead, zinc yellow, chromium oxide, ferric oxide, iron oxide black, copper oxide, magnesium oxide, magnesium hydroxide, strontium titanate, yttrium oxide, hafnium oxide, niobium oxide, tantalum oxide (Ta2O5), barium oxide, indium oxide, europium oxide, lanthanum oxide, zircon, tin oxide, and lead oxide, as well as composite oxides thereof such as lithium niobate, potassium niobate, lithium tantalate, and aluminum magnesium oxide (MgAl2O4). In addition, rare earth oxides can be used as high refractive index components, such as scandium oxide, yttrium oxide, lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, samarium oxide, europium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, holmium oxide, erbium oxide, thulium oxide, ytterbium oxide, and lutetium oxide. Of the many options mentioned above, zirconia (zirconium oxide) is preferred for the high refractive index member.
[0064] The high refractive index member is preferably a particulate member. The particle size (diameter) of the particulate high refractive index member is not particularly limited, but is, for example, 1 to 100 nm, preferably 5 to 50 nm, more preferably 7.5 to 30 nm, and particularly preferably 10 to 25 nm. In addition, the high refractive index member, which is, for example, particulate, preferably includes a coating of an organic layer as a surface treatment layer that covers the outer surface of a metal oxide, etc. The coating of the organic layer improves the compatibility of the high refractive index member with the resin material that forms the high refractive index layer, and allows the high refractive index member to be firmly bonded to the resin material. The surface treatment layer is preferably a coating of an organic layer having an ultraviolet-reactive (curing) functional group introduced onto the surface.
[0065] The high refractive index layer preferably contains the second resin material and the high refractive index member in a weight ratio of 10:90 to 40:60, and the ratio of the second resin material to the high refractive index member is more preferably 15:85 to 35:65, and even more preferably 20:80 to 30:70.
[0066] The thickness of the high refractive index layer is not particularly limited, but is preferably 10 to 300 nm, more preferably 50 to 250 nm, further preferably 100 to 180 nm, and particularly preferably 130 to 170 nm.
[0067] When the optical interference layer has a low refractive index layer and a high refractive index layer, the high refractive index layer is preferably laminated between the substrate layer and the low refractive index layer. In the antireflection film having such a laminate structure, the reflectance of the entire film can be reliably reduced.
[0068] Other Ingredients The high refractive index layer or the second resin material forming the high refractive index layer preferably contains at least one of a photoinitiator and a leveling agent, and more preferably contains a photoinitiator. In addition, the second resin material may contain a solvent. Examples of the leveling agent include a fluorine-based leveling agent, an acrylic-based leveling agent, and a silicone-based leveling agent.
[0069] <Uncured hard coat layer> The laminate for an antireflection film has an uncured hard coat layer. When the uncured hard coat layer is cured to provide a hard coat layer in the antireflection film obtained from the laminate for an antireflection film, the surface hardness and scratch resistance are improved.
[0070] The uncured hard coat layer is preferably laminated on the opposite side of the substrate film side of the above-mentioned optical interference layer.For example, the uncured hard coat layer is laminated so as to be in contact with the optical interference layer, and is preferably pressed onto the optical interference layer.However, other layers, such as an adhesive layer, the details of which will be described later, may be provided between the uncured hard coat layer and the optical interference layer. In addition, the uncured hard coat layer is preferably laminated between the substrate layer and the optical interference layer.For example, in the laminate for antireflection film that includes a low refractive index layer, a high refractive index layer, and a hard coat layer, the hard coat layer is preferably laminated between the substrate layer and the high refractive index layer.That is, in the laminate for antireflection film that has a substrate layer, a low refractive index layer, a high refractive index layer, and a hard coat layer, these layers are preferably laminated in the order of the substrate layer, the hard coat layer, the high refractive index layer, and the low refractive index layer.
[0071] The uncured hard coat layer has a curable hard coat composition. The uncured hard coat layer is preferably formed on the surface of a substrate layer, the details of which will be described later. That is, the uncured hard coat layer is preferably formed by applying a hard coat material that can be cured by heat or active energy rays onto the surface of the substrate layer.
[0072] The hard coat composition preferably contains at least one of an acrylate monomer and an acrylate oligomer, and more preferably contains at least a urethane acrylate oligomer. An example of a coating material that can be used as a hard coat composition and that can be cured by active energy rays is a resin composition consisting of a single or multiple monofunctional or polyfunctional acrylate monomers or oligomers, more preferably a resin composition containing a urethane acrylate oligomer, etc. It is preferable to add a photopolymerization initiator as a curing catalyst to these resin compositions.
[0073] An example of a hard coat coating material that is cured using active energy rays is one in which 1 to 10 parts by weight of a photopolymerization initiator is added to 100 parts by weight of a photopolymerizable resin composition obtained by mixing 40 to 95% by weight of a hexafunctional urethane acrylate oligomer and about 5 to 60% by weight of a (meth)acrylate such as 2-(2-vinyloxyethoxy)ethyl (meth)acrylate [2-(2-vinyloxyethoxy)ethyl acrylate: VEEA].
[0074] As the photopolymerization initiator, generally known ones can be used, specifically, benzoin, benzophenone, benzoin ethyl ether, benzoin isopropyl ether, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, azobisisobutyronitrile, benzoyl peroxide, etc.
[0075] Examples of thermosetting resin coatings that can be used as hard coat compositions include polyorganosiloxane-based, crosslinked acrylic-based, etc. Some of these resin compositions are commercially available as hard coat agents for acrylic resins or polycarbonate resins, and can be selected appropriately taking into account suitability for the coating line.
[0076] The uncured hard coat layer preferably contains a curable tack-free hard coat composition. When a hard coat composition having excellent tack-free properties is used, the hard coat composition can maintain a predetermined shape even in an uncured state when it comes into contact with other substances such as the hands of a worker, and the adhesion of a part of the hard coat composition to the surface of the contacted substance is suppressed. Thus, according to the tack-free hard coat composition, the hard coat composition can be easily processed to be cured after being molded into a shape suitable for various applications. In addition, the hard coat composition in a pre-cured state can be easily stored or distributed in a predetermined shape. In contrast, resin compositions with poor tack-free properties, such as resin compositions mainly composed of low molecular weight oligomers, require a curing step before being molded into shapes suitable for various applications, and therefore tend to have poor moldability.
[0077] The tack-free hard coat composition has a curing property that allows it to be cured by irradiation with energy rays, etc., and preferably contains a (meth)acryloyl polymer and inorganic oxide nanoparticles. As will be described in detail later, the hard coat composition has excellent moldability and tack-free property before curing, and when cured to form a hard coat layer, it can achieve high hardness and scratch resistance.
[0078] The hard coat composition preferably contains 20-80% by weight of (meth)acryloyl polymer and 80-20% by weight of inorganic oxide nanoparticles based on the total weight of the hard coat composition, more preferably 30-70% by weight of (meth)acryloyl polymer and 70-30% by weight of inorganic oxide nanoparticles, and even more preferably 40-60% by weight of (meth)acryloyl polymer and 60-40% by weight of inorganic oxide nanoparticles.
[0079] (Meth)acryloyl polymer The (meth)acryloyl polymer preferably has a (meth)acrylic equivalent of 200 to 500 g / eq. The (meth)acrylic equivalent of the (meth)acryloyl polymer is preferably 220 to 450 g / eq, and more preferably 250 to 400 g / eq. The (meth)acryloyl polymer also preferably has a double bond equivalent of 100 to 1000 g / eq, and the double bond equivalent of the (meth)acryloyl polymer is more preferably 150 to 800 g / eq, further preferably 200 to 600 g / eq, and particularly preferably 250 to 400 g / eq. The (meth)acryloyl polymer preferably has a weight average molecular weight of 5,000 to 200,000. The weight average molecular weight of the (meth)acryloyl polymer is preferably 10,000 to 150,000, more preferably 15,000 to 100,000, and even more preferably 18,000 to 50,000. The value of the weight average molecular weight can be measured based on the description in paragraphs 0061 to 0064 of JP-A-2007-179018. Details of the measurement method are shown below. [Table 1] In this specification, (meth)acrylic includes both acrylic and methacrylic.
[0080] As described above, a hard coat composition containing a (meth)acryloyl polymer having a (meth)acrylic equivalent and weight average molecular weight within a specified range has good tack-free properties before curing and good scratch resistance after curing, and is also capable of easily progressing the curing and polymerization reaction.
[0081] The (meth)acryloyl polymer contained in the hard coat composition preferably has a repeating unit represented by the following formula (I). [ka] In formula (I), m is an alkylene group having 1 to 4 carbon atoms or a single bond, n is an alkyl group having 1 to 4 carbon atoms or hydrogen, p is a single bond or an alkylene group having 1 or 2 carbon atoms, and q is an alkyl group having a total of 1 to 12 carbon atoms which may contain at least one substituent selected from the group consisting of an epoxy group, a hydroxyl group, an acryloyl group, and a methacryloyl group, or hydrogen.
[0082] The (meth)acryloyl polymer more preferably contains the following repeating unit, that is, a repeating unit in which, in the above formula (I), m is an alkylene group having 1 or 2 carbon atoms, n is an alkyl group having 1 or 2 carbon atoms, p is a single bond or a methylene group, and q is an alkyl group having a total of 1 to 6 carbon atoms which may contain at least any one of substituents selected from a glycidyl group, a hydroxyl group, and an acryloyl group, or hydrogen. For example, in the above formula (I), m is a methylene group, n is a methyl group, p is a single bond, and q is a methyl group, an alkyl group having 5 or less carbon atoms and containing a glycidyl group (epoxy group), an alkyl group having 8 or less carbon atoms and containing a hydroxyl group and an acryloyl group, or the like.
[0083] Specific examples of the repeating units contained in the (meth)acryloyl polymer include those represented by the following formulae (II-a), (II-b), and (II-c). [ka] In the (meth)acryloyl polymer, the repeating unit of the formula (II-a) is preferably 30 to 85 mol %, more preferably 40 to 80 mol %, based on the total number of moles of the repeating unit of the formula (II-a), the repeating unit of the formula (II-b), and the repeating unit of the formula (II-c). The repeating unit of the formula (II-b) is preferably 5 to 30 mol %, more preferably 10 to 25 mol %, based on the total number of moles. The repeating unit of the formula (II-c) is preferably 10 to 40 mol %, more preferably 10 to 35 mol %, based on the total number of moles. The molar ratio of the repeating unit of the above formula (II-a), the repeating unit of the above formula (II-b) and the repeating unit of the above formula (II-c) is preferably 5:2:3.
[0084] A pentaerythritol-based polyfunctional acrylate compound may be added to the (meth)acryloyl polymer. Examples of the polyfunctional acrylate compound include pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate, which are represented by the following formulae (III-a) and (III-b), respectively, as well as pentaerythritol triacrylate. [ka]
[0085] The polyfunctional acrylate compound is preferably contained in an amount of 70% by weight or less, more preferably 50% by weight or less, based on the total weight of the polyfunctional acrylate compound and the (meth)acryloyl polymer. In this way, by adding the polyfunctional acrylate compound to the hard coat composition and reacting it with the acryloyl group, glycidyl group (epoxy group), and hydroxyl group contained in the side chain of the (meth)acryloyl polymer, a hard coat film having higher scratch resistance can be formed.
[0086] Inorganic oxide nanoparticles As the inorganic oxide nanoparticles contained in the hard coat composition, silica particles, alumina particles, etc. can be used. Among these, it is preferable that the inorganic oxide nanoparticles contain silica particles, and it is preferable that the silica particles contain at least colloidal silica. The inorganic oxide nanoparticles contained in the hard coat are preferably treated with a surface treatment agent, which allows the inorganic oxide nanoparticles to be stably dispersed in the hard coat composition, particularly in the (meth)acryloyl polymer component.
[0087] As a surface treatment agent for inorganic oxide nanoparticles, a compound having a substituent that can be bonded to the surface of inorganic oxide nanoparticles and a substituent that is highly compatible with the components of the hard coat composition that disperses inorganic oxide nanoparticles, particularly with (meth)acryloyl polymers, is preferably used. For example, a silane compound, alcohol, amine, carboxylic acid, sulfonic acid, phosphonic acid, etc. are used as the surface treatment agent.
[0088] The inorganic oxide nanoparticles preferably have a copolymerizable group on the surface. The copolymerizable group can be introduced by surface treatment of the inorganic oxide nanoparticles. Specific examples of the copolymerizable group include a vinyl group, a (meth)acrylic group, and a free radical polymerizable group. The average particle size of the inorganic oxide nanoparticles is from 6 to less than 95 nm, more preferably from 7 to 50 nm, and further preferably from 8 to 20 nm. In order to prevent the occurrence of irregularities on the surface of the hard coat composition after curing and to obtain a good surface appearance, it is preferable to use inorganic oxide nanoparticles that are in a state of as little aggregation as possible.
[0089] Other components in the tack-free hard coat composition The tack-free hard coat composition preferably further contains a leveling agent in addition to the above-mentioned (meth)acryloyl polymer and inorganic oxide nanoparticles. As the leveling agent, for example, a silicon-based surfactant, an acrylic-based surfactant, a fluorine-based surfactant, etc. are preferably used.
[0090] The hard coat composition preferably contains 0.1 wt % or more and 10 wt % or less of a leveling agent based on the total weight of the hard coat composition, and the content of the leveling agent in the hard coat composition is more preferably 0.5 wt % or more and 7 wt % or less, and even more preferably 1 wt % or more and 5 wt % or less.
[0091] In addition to an organic solvent, various stabilizers such as an ultraviolet absorber, a light stabilizer, and an antioxidant, and surfactants such as a leveling agent, a defoamer, a thickener, an antistatic agent, and an antifogging agent may be appropriately added to the hard coat composition as necessary.
[0092] The refractive index of the uncured hard coat layer is preferably approximately the same as that of the base layer. Specifically, the refractive index of the uncured hard coat layer is preferably in the range of 1.49 to 1.65. The refractive index of the uncured hard coat layer is more preferably 1.49 to 1.60, further preferably 1.51 to 1.60, and particularly preferably about 1.53 to 1.59. The difference between the refractive index of the substrate layer and the refractive index of the uncured hard coat layer is preferably 0.04 or less, more preferably 0.03 or less, and even more preferably 0.02 or less.
[0093] The thickness of the uncured hard coat layer is not particularly limited, but is preferably about 1 to 10 μm, more preferably about 2 to 8 μm, and further preferably about 3 to 7 μm.
[0094] <Base material layer> The substrate layer included in the laminate for antireflection films is disposed on the side of the uncured hard coat layer opposite to the optical interference layer, and is preferably laminated so as to be in contact with the uncured hard coat layer. The substrate layer is preferably disposed on the outermost side of the laminate for antireflection films.
[0095] The base layer includes a thermoplastic resin, for example, a transparent resin. The type of thermoplastic resin is not particularly limited, and various resins such as polycarbonate (PC) resin, acrylic resin such as polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyimide (PI), cycloolefin copolymer (COC), norbornene-containing resin, polyethersulfone, cellophane, aromatic polyamide, etc. Of these options, it is preferable that the thermoplastic resin of the base layer contains at least a polycarbonate resin.
[0096] The type of polycarbonate resin contained in the base layer is not particularly limited as long as it contains a -[OR-OCO]- unit (wherein R contains an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and further has a straight-chain structure or a branched structure) containing a carbonate bond in the molecular main chain, but polycarbonates having a bisphenol skeleton are preferred, and polycarbonates having a bisphenol A skeleton or a bisphenol C skeleton are particularly preferred. As the polycarbonate resin, a mixture or copolymer of bisphenol A and bisphenol C may be used. By using a bisphenol C-based polycarbonate resin, for example, a polycarbonate resin containing only bisphenol C, or a mixture or copolymer of bisphenol C and bisphenol A, the hardness of the base layer can be improved. can. The viscosity average molecular weight of the polycarbonate resin is preferably from 15,000 to 40,000, more preferably from 20,000 to 35,000, and further preferably from 22,500 to 25,000.
[0097] The acrylic resin contained in the base layer is not particularly limited, but may be, for example, a homopolymer of various (meth)acrylic acid esters such as polymethyl methacrylate (PMMA) or methyl methacrylate (MMA), or a copolymer of PMMA or MMA with one or more other monomers, or a mixture of a plurality of these resins. Among these, a (meth)acrylate containing a cyclic alkyl structure, which has low birefringence, low moisture absorption, and excellent heat resistance, is preferred. Examples of such (meth)acrylic resins include, but are not limited to, Acrypet (manufactured by Mitsubishi Rayon), Delpet (manufactured by Asahi Kasei Chemicals), and Parapet (manufactured by Kuraray). In addition, the use of a mixture containing a polycarbonate resin and the above-mentioned acrylic resin is preferable in that the hardness of the substrate layer, particularly the surface layer of the substrate layer, and particularly the outermost layer of the laminate for an antireflection film can be improved.
[0098] The substrate layer may also contain additives other than the thermoplastic resin, such as at least one additive selected from the group consisting of a heat stabilizer, an antioxidant, a flame retardant, a flame retardant assistant, an ultraviolet absorber, a release agent, and a colorant. In addition, antistatic agents, fluorescent brighteners, antifogging agents, flow improvers, plasticizers, dispersants, antibacterial agents, and the like may also be added to the substrate layer.
[0099] The base layer preferably contains 80% by mass or more of a thermoplastic resin, more preferably 90% by mass or more, and particularly preferably 95% by mass or more of a thermoplastic resin. The base layer preferably contains 80% by mass or more of a polycarbonate resin, more preferably 90% by mass or more, and particularly preferably 95% by mass or more of a polycarbonate resin, among the thermoplastic resins of the base layer.
[0100] The substrate layer preferably has a refractive index in the range of 1.49 to 1.65, more preferably 1.49 to 1.60, further preferably 1.51 to 1.60, and particularly preferably about 1.53 to 1.59.
[0101] The thickness of the substrate layer is not particularly limited, but is preferably 50 to 500 μm, more preferably 70 to 400 μm, and particularly preferably 100 to 300 μm. In addition, the laminate for antireflection film may have two or more substrate layers, and when a plurality of substrate layers are provided, the total thickness of the substrate layers is, for example, 100 to 1000 μm, and preferably about 200 to 500 μm.
[0102] Examples of the substrate layer including the above-mentioned multiple layers, that is, the substrate layer as a multi-layer laminate, include the following: A layer of the above-mentioned polycarbonate resin (PC), such as bisphenol A, is laminated with an acrylic resin layer such as the above-mentioned acrylic resin, such as poly(methyl meth)acrylate resin (PMMA: polymethyl acrylate and / or polymethyl methacrylate), as a surface layer (layer on the low refractive index layer side); a layer of a polycarbonate resin (PC) such as bisphenol A is laminated with a polycarbonate resin (PC) such as bisphenol C, etc. In a laminate in which a layer of a polycarbonate resin (PC) containing bisphenol A is laminated with a polycarbonate resin (PC) containing bisphenol C, for example, a polycarbonate resin containing bisphenol C is used as the surface layer. It is also preferable to use a surface layer having a high hardness, particularly a hardness higher than that of the other substrate layers.
[0103] The polycarbonate resin, which is a thermoplastic resin used in the laminate, is preferably the above-mentioned one, as well as the polycarbonate resin forming the single-layer substrate layer. For example, a mixture or copolymer of bisphenol A and bisphenol C may be used. By using a bisphenol C-based polycarbonate resin, for example, a polycarbonate resin containing only bisphenol C, or a mixture or copolymer of bisphenol C and bisphenol A, it is possible to improve the hardness of the surface layer (the layer on the low refractive index layer side) of the substrate layer, which is a laminate. In order to further improve the hardness, a mixture of the above-mentioned acrylic resin and a polycarbonate resin, for example, a bisphenol C-based polycarbonate resin, may be used.
[0104] <Adhesive layer> The laminate for anti-reflection film preferably has an adhesive layer. The adhesive layer is preferably laminated between the optical interference layer and the uncured hard coat layer in the laminate for anti-reflection film. When the adhesive layer is provided, the first laminate having the adhesive layer and the second laminate having the uncured hard coat layer can be reliably laminated, preferably pressed, in the manufacturing process of the laminate for anti-reflection film, which will be described in detail later. In the laminate for an anti-reflection film provided with an adhesive layer, the uncured hard coat layer preferably has a tack-free hard coat composition.
[0105] The adhesive layer preferably contains an oligomer and / or polymer having a urethane bond, which is a reaction product between an acrylate compound and an isocyanate compound. More specifically, the adhesive layer preferably contains an oligomer and / or polymer having a urethane bond, which is a reaction product between an oligomer and / or polymer of an acrylate compound having at least one hydroxyl group and an isocyanate compound having at least one isocyanate group that bonds with the hydroxyl group to generate a urethane bond. The weight average molecular weight of the oligomer and / or polymer having a urethane bond is preferably from 1,000 to 100,000, more preferably from 1,200 to 50,000, and even more preferably from 1,400 to 30,000.
[0106] The above-mentioned acrylate compound forming the adhesive layer is preferably an alkyl acrylate compound having 30 or less carbon atoms, more preferably an alkyl acrylate compound having 20 or less carbon atoms, and even more preferably an alkyl acrylate compound having 15 or less carbon atoms. In addition, the above-mentioned isocyanate compound forming the adhesive layer is preferably an isocyanate compound having a methacryl group and having 20 or less carbon atoms, more preferably an isocyanate compound having 15 or less carbon atoms, and even more preferably an isocyanate compound having 10 or less carbon atoms.
[0107] The adhesive layer preferably contains an oligomer and / or polymer having a urethane bond represented by the following formula (1). [ka] In the above formula (1), n is an integer of 1 to 20, preferably an integer of 1 to 12, and more preferably an integer of 1 to 8.
[0108] The adhesive layer may also contain components other than the oligomer and / or polymer having a urethane bond, such as at least one additive selected from the group consisting of a heat stabilizer, an antioxidant, a flame retardant, a flame retardant assistant, an ultraviolet absorber, a release agent, and a colorant. In addition, an antistatic agent, a fluorescent brightener, an antifogging agent, a flow improver, a plasticizer, a dispersant, an antibacterial agent, and the like may also be added to the adhesive layer.
[0109] The adhesive layer preferably has a refractive index in the range of 1.49 to 1.65, more preferably 1.49 to 1.60, further preferably 1.51 to 1.60, and particularly preferably about 1.53 to 1.59.
[0110] The thickness of the adhesive layer is not particularly limited, but is preferably about 1 to 10 μm, more preferably about 2 to 8 μm, and further preferably about 3 to 7 μm.
[0111] <Additional layer> In the laminate for an antireflection film, a layer (additional layer) other than the above-mentioned layers may be further laminated. The thickness of the additional layer is not particularly limited, but is preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm.
[0112] [2. Manufacturing method of laminated film for anti-reflection film] The method for producing the laminate film for an antireflection film of the present invention is as follows.
[0113] The method for producing the laminate film for anti-reflection film of the first embodiment includes the steps of: a first lamination step of laminating an optical interference layer on a release surface of a substrate film to form a first laminate; and a second lamination step of laminating an uncured hard coat layer having a curable hard coat composition on one surface of the substrate layer containing a thermoplastic resin to form a second laminate.
[0114] In the second lamination step, for example, as shown in Fig. 1, a laminate of a methacrylic resin layer as a first substrate layer 12 and a polycarbonate resin layer as a second substrate layer 14 is used as a substrate layer, and a hard coat composition is applied, for example, onto the surface of the substrate layer on the first substrate layer 12 side to form an uncured hard coat layer 20. In this way, a second laminate 10 is obtained.
[0115] In the manufacture of the substrate layer, for example, a resin composition material such as a methacrylic resin or a polycarbonate resin is processed into a layer (sheet) by a conventional method. For example, this is a method using extrusion molding or cast molding. An example of extrusion molding is a method in which pellets, flakes, or powder of the resin composition of the present invention is melted and kneaded in an extruder, extruded from a T-die or the like, and the resulting semi-molten sheet is cooled and solidified while being pressed between rolls to form a sheet.
[0116] 2, the material of the optical interference layer 30 is applied onto the release surface 16A of the base film 16 to form the optical interference layer 30, thereby obtaining a first laminate 40. As the material for forming the optical interference layer 30, for example, a curable low refractive index paint, a high refractive index paint, or the like is used. As illustrated in Figure 3, a release layer 18 may be laminated onto a base film 16, and an optical interference layer 30 may be formed on the surface of the release layer 18 opposite the base film 16 to form a first laminate 40. In producing the base film, for example, a resin composition such as PET is processed into a layer (sheet) by a conventional method, and a release agent is applied to the surface of the layer to form a release surface or layer.
[0117] The manufacturing method of the first embodiment further includes a third lamination step of laminating, preferably pressing, the first and second laminates together so that the optical interference layer of the first laminate contacts the uncured hard coat layer of the second laminate. For example, in the third lamination step, as shown in FIG. 4, the first laminate 40 and the second laminate 10 are laminated so that the optical interference layer 30 and the uncured hard coat layer 20 are in contact with each other.
[0118] The method for producing the laminate film for an antireflection film of the second embodiment is different from the first embodiment in that a step of laminating an adhesive layer is added. That is, the second embodiment of the manufacturing method is as follows: a first lamination step of laminating an optical interference layer on a release surface of a substrate film, and laminating an adhesive layer on a surface of the optical interference layer opposite to the release surface (on the surface of the optical interference layer); and a second lamination step of laminating an uncured hard coat layer having a curable, tack-free hard coat composition on one surface of the substrate layer containing a transparent resin to form a second laminate. Furthermore, the manufacturing method of the second embodiment has a third lamination step of laminating, preferably pressing, the first and second laminates so that the adhesive layer of the first laminate contacts the uncured hard coat layer of the second laminate.
[0119] In both the first and second embodiments, it is preferable that the first lamination step further includes a first curing step of laminating a curable optical interference layer and curing the optical interference layer between the first lamination step and the second lamination step. In either the first or second embodiment, it is preferable to further include a second curing step of curing the uncured hard coat layer after the third lamination step. In this way, by laminating the uncured hard coat layer in the second lamination step, good moldability of the laminate film for antireflection film can be achieved before the second curing step of curing the uncured hard coat layer is performed. Then, by forming, for example, thermoforming, the laminate film for antireflection film and then performing the second curing step, the desired shape of the antireflection film can be easily achieved.
[0120] The temperature during lamination of the first and second laminates in the third lamination step, preferably during compression bonding, is preferably 20 to 100° C. in both the first and second embodiments. The temperature during compression bonding is more preferably 40 to 80° C., and further preferably 50 to 70° C. In the third lamination step, the first and second laminates are preferably bonded together by applying a pressure of 4 MPa or less, and the pressure is, for example, 0.5 MPa or more and 4 MPa or less. More preferably, the pressure for bonding the first and second laminates together is 1.0 MPa or more and 3.0 MPa or less. When the first and second laminates are pressure-bonded, it is preferable that the first and second laminates are pressed by upper and lower rolls while passing through a gap between these rolls.
[0121] [3. Anti-reflective film] The anti-reflection film of the present invention has the above-mentioned laminate for anti-reflection film. The anti-reflection film is produced, for example, by subjecting the above-mentioned laminate for anti-reflection film to a process of thermoforming and ultraviolet curing. In the laminate for anti-reflection film, the substrate film, which preferably forms the outermost layer, may be peeled off from the release surface and removed to obtain the anti-reflection film.
[0122] The antireflection film preferably has a cured hard coat layer formed by curing the uncured hard coat layer contained in the above-mentioned laminate for an antireflection film. In the anti-reflection film, the refractive index of the substrate layer is 1.49 to 1.65, and the difference between the refractive index of the substrate layer and that of the cured hard coat layer is preferably 0.04 or less. The cured hard coat layer has a refractive index value that is approximately 0.02 higher than that of the uncured hard coat layer. In the antireflection film, the optical interference layer has a low refractive index layer having a lower refractive index than the substrate layer, and the substrate layer preferably has a refractive index of 1.49 to 1.65 and the low refractive index layer preferably has a refractive index of 1.31 to 1.41.
[0123] [4. Properties of laminated film for anti-reflection film and anti-reflection film] <Reflectance (luminous reflectance)> The luminous reflectance of the surface of the antireflection film on the optical interference layer side, measured under the conditions of JIS Z 8722 2009, is preferably 3.0% or less, more preferably 2.5% or less, and even more preferably 1.6% or less.
[0124] <Pencil hardness> The surface of the antireflection film facing the optical interference layer preferably has a high hardness. Specifically, the pencil hardness of the surface facing the optical interference layer, as defined by JIS K-5400, is preferably 3B or more, more preferably 2B or more, even more preferably F or more, and particularly preferably 2H or more.
[0125] <Scratch resistance> The surface of the antireflection film on the optical interference layer side is preferably excellent in abrasion resistance. Specifically, the absolute value of the haze change (ΔH), which is the difference between the haze value measured before the abrasion test and the haze value measured after the abrasion test according to JIS K 7136:2000, is preferably less than 2.0%.
[0126] <Thermoformability (moldability including deep drawability and right-angle shape forming ability)> As described in detail below, the use of a laminate for an anti-reflection film to obtain a compressed air molded body with a sufficiently small value of corner radius R means that the laminate for an anti-reflection film is easily shaped to fit the right-angled areas of the mold, and has excellent deep drawability and right-angle shape forming properties.
[0127] <Film surface condition> In the laminate for antireflection film, it is preferable that the surface, particularly the surface on the optical interference layer side, is in a good condition. Specifically, even after the process of applying a resin material for forming an optical interference layer, drying and curing, it is preferable that cracks, whitening, foaming and unevenness (mainly color unevenness) are not observed on the surface of the laminate for antireflection film, and the appearance of the obtained surface is good.
[0128] <Growth rate> The laminate for anti-reflection film is also excellent in elongation during molding. Specifically, similarly to the evaluation of thermoformability, the polycarbonate resin (base layer) side of a sample cut to 210 mm x 297 mm x 0.3 mm (thickness) is preheated at 190°C for 40 seconds, the sample is placed in a mold having a right-angled protrusion with a deep drawing height of 13 mm and both vertical and horizontal lengths of 30 mm so that the base layer is in contact with the sample, and pressure molding of the sample is performed using high-pressure air of 1.5 MPa, and the obtained pressure-molded body preferably has a radius R of 3.0 mm or less in the region in contact with the right-angled protrusion of the mold.
[0129] Furthermore, when the above-mentioned pressure molding is performed, it is preferable that the value of the elongation percentage calculated as follows is sufficiently large. That is, lattice lines with a predetermined interval, for example, 1 mm, are printed on the sample surface of the laminate for antireflection film, and the elongation percentage is calculated by the following formula (III) based on how much the interval between the predetermined lattice lines has increased after pressure molding compared to before pressure molding. (Spacing of the grid lines after pressure forming (mm)) - spacing of the grid lines before pressure forming (mm) / spacing of the grid lines before pressure forming (mm) × 100 (%) Formula (III) The above formula (III) can be said to be equivalent to a formula showing (length between two specified points after pressure forming - length between the two points before pressure forming) / (length between the two points before pressure forming) x 100 (%).
[0130] Using the above formula (III), the elongation rate (%) of a certain region after pressure forming can be calculated after arranging the antireflection film before pressure forming so as to cover a right-angled part having a deep drawing height of 13 mm. As illustrated in Fig. 5, if lattice lines, each with an interval of 1 mm, are printed on the surface of the laminate for antireflection film before pressure forming, and the interval of the lattice lines in a certain region after pressure forming, for example, the region surrounded by a diamond in Fig. 6, is 2 mm, the elongation rate is calculated by the above formula (III) as (2(mm)-1(mm)) / 1(mm)×100=100(%).
[0131] It is preferable that the laminate for an antireflection film is moldable so that the value of the elongation calculated based on the above formula (III) is sufficiently large. For example, the above elongation percentage (%) is preferably at least 10 times the deep drawing height (mm) of the die, and more preferably at least 14 times the deep drawing height (mm).
[0132] [Laminated film] A laminate film can also be produced using the antireflection film of the present invention. For example, it is a laminate film having a transparent resin substrate and the above-mentioned antireflection film. As the transparent resin substrate, for example, a substrate in which a methacrylic resin layer is laminated on a polycarbonate layer of bisphenol A, and a substrate in which a polycarbonate layer of bisphenol C is laminated on a polycarbonate layer of bisphenol A are used. The thickness of the transparent resin substrate is not particularly limited, but is preferably 30 to 1000 μm (1 mm), more preferably 50 to 700 μm, and further preferably 100 to 500 μm.
[0133] Examples of laminate films include films that are attached to the surfaces of computer screens, television screens, plasma display panels, etc., and films that are used on the surfaces of polarizing plates used in liquid crystal display devices, sunglasses lenses, prescription eyeglass lenses, camera viewfinder lenses, various instrument covers, automobile glass, train glass, in-vehicle display panels, electronic device housings, etc. EXAMPLES
[0134] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be modified as desired without departing from the gist of the present invention.
[0135] <Base material layer> The substrate layer used was a transparent substrate layer (DF02 manufactured by MGC Filsheet Co., Ltd.; total thickness 300 μm) in which a methacrylic resin layer was laminated onto a polycarbonate resin layer made of 2,2-bis(4-hydroxyphenyl)propane (bisphenol A). Of these substrate layers, the polycarbonate resin layer had a refractive index of 1.584, and the methacrylic resin layer had a refractive index of 1.491.
[0136] <Low refractive index paint> To form a low refractive index layer, a curable low refractive index coating material was prepared as follows. First, dry air was introduced into a five-neck flask equipped with a stirrer, a thermometer, a cooler, a monomer dropping funnel, and a dry air inlet tube to dry the system. Then, 58.9 parts by weight of 2,2,3,3-tetrafluoro-1,4-butanediol (C4DIOL manufactured by Exfluor Research Corporation), 279.8 parts by weight of pentaerythritol triacrylate, 0.5 parts by weight of dibutyltin lauryl as a polymerization catalyst, and 500 parts by weight of methyl ethyl ketone as a solvent were added to the five-neck flask and heated to 60°C. After that, 161.3 parts by weight of isophorone diisocyanate was added to the reaction system and reacted at 60 to 70°C. The consumption of the isocyanate residues in the reaction product was confirmed by infrared absorption spectroscopy, and the reaction was terminated to obtain a hexafunctional urethane acrylate oligomer. Furthermore, 2-(2-vinyloxyethoxy)ethyl acrylate (VEEA) was mixed into the reaction system so that the ratio of the urethane acrylate oligomer (urethane acrylate liquid) was urethane acrylate liquid / VEEA=90 / 10 (wt%).
[0137] Hollow silica (JGC Catalysts and Chemicals Sururia 4320) was added to the liquid component of the resin material thus obtained, and mixed at a ratio of resin material / hollow silica = 35 / 65 (wt%). Furthermore, 5 wt% of 1-hydroxy-cyclohexyl-phenyl-ketone (BASF I-184) was added as a photoinitiator, and 1 wt% of leveling agent RS-78 (DIC: solid content as leveling agent is 40 wt% and diluted with solvent MEK) was added and dissolved, and a solvent (propylene glycol monomethyl ether) was added to adjust the concentration so that the solid content was 1.5 wt%. The obtained product was used as a low refractive index paint for the low refractive index layer (hereinafter also referred to as low refractive index paint B). The resin material of the low refractive index paint, i.e., the refractive index before the addition of hollow silica, was 1.486, and the refractive index of low refractive index paint B after the addition of hollow silica was 1.3651.
[0138] <High refractive index paint> First, dry air was introduced into a 3L five-neck flask equipped with a stirrer, a thermometer, a condenser, a dropping funnel, and a dry air inlet tube to dry the inside of the system. Then, 553 parts by weight of 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (TBIS-G manufactured by Taoka Chemical Co., Ltd.), 592 parts by weight of 2-hydroxy-3-phenoxypropyl acrylate (M-600A manufactured by Kyoeisha Chemical Co., Ltd.), 1.5 parts by weight of dibutyltin laurate as a polymerization catalyst, 3 parts by weight of 2,6-tert-butyl-4-methylphenol (BHT), and 1500 parts by weight of methyl ethyl ketone as a solvent were added to the five-neck flask, mixed uniformly, and heated to 60°C. Thereafter, 448 parts by weight of xylylene diisocyanate (XDI manufactured by Mitsui Chemicals, Inc.) was further added to the reaction system, and the reaction was allowed to proceed at 70° C. It was confirmed by infrared absorption spectroscopy that the isocyanate residues in the reaction product had been consumed, and the reaction was terminated to obtain a bifunctional urethane acrylate oligomer.
[0139] The liquid component of the resin material thus obtained, i.e., the bifunctional urethane acrylate oligomer (urethane acrylate liquid), was mixed with 2-(2-vinyloxyethoxy)ethyl acrylate (VEEA) at a ratio of urethane acrylate liquid / VEEA = 90 / 10 (wt%). Zirconia (manufactured by Nippon Shokubai Co., Ltd.) was added to this resin material at a ratio of resin material / zirconia = 20 / 80 (wt%) and mixed. Furthermore, 5% by weight of 1-hydroxy-cyclohexyl-phenyl-ketone (I-184 manufactured by BASF) was dissolved as a photoinitiator in the reaction system, and a solvent (propylene glycol monomethyl ether) was added to adjust the concentration so that the solid content was 7% by weight. The resulting product was used as a high refractive index paint for the high refractive index layer (hereinafter also referred to as high refractive index paint A).
[0140] The refractive index of the resin material of the high refractive index paint, i.e., the resin material before the addition of zirconia, was 1.5580, and the refractive index of high refractive index paint A after the addition of zirconia was 1.7196.
[0141] <Hard Coat Composition> A functional urethane acrylate oligomer (urethane acrylate liquid: CN-968 manufactured by Sartomer Corporation) was mixed with 2-(2-vinyloxyethoxy)ethyl (meth)acrylate (VEEA) at a ratio of urethane acrylate liquid / VEEA=50 / 50 (wt%). The liquid component of the resin material thus obtained was mixed with 5% by weight of 1-hydroxy-cyclohexyl-phenyl-ketone (I-184, manufactured by BASF) as a photoinitiator. The hard coat composition thus obtained had a refractive index of 1.4900.
[0142] [Example 1] The above-mentioned low refractive index paint was applied to the release surface of a 50 μm-thick release PET film (base film: TR manufactured by Nippa Corporation) so that the dry coating film thickness was 100 nm, and then dried at 100° C. for 2 minutes. After that, an ultraviolet curing device was used to apply an integrated light dose of 500 mJ / cm to the dry coating film side of the release PET film. 2 The sample was irradiated with ultraviolet light. On the other hand, the above-mentioned hard coat composition (hard coat paint) was applied to the surface of the methacrylic resin layer of the above-mentioned base layer so that the dry coating thickness was 4 μm, and dried for 2 minutes at 100° C. At this stage, the hard coat composition was not cured. The two laminates were brought into contact with each other so that the coating surface of the low refractive index paint and the coating surface of the hard coat composition overlapped each other, and then pressed together at 60°C and 1.0 MPa to obtain a laminate for an anti-reflection film, which was then molded using a pressure molding machine. 2 The laminate was cured at 40° C. to obtain an anti-reflection film.
[0143] [Example 2] The above-mentioned low refractive index paint was applied to the release surface of a 50 μm-thick release PET film (base film: TR manufactured by Nippa Corporation) so that the dry coating film thickness was 100 nm, and then dried at 100° C. for 2 minutes. After that, an ultraviolet curing device was used to apply an integrated light dose of 500 mJ / cm to the dry coating film side of the release PET film. 2Further, a high refractive index paint was applied on the dried coating film of the low refractive index paint so that the dried coating film thickness was 150 nm, and dried at 100°C for 2 minutes. After that, a UV curing device was used to irradiate the coating film side of the high refractive index paint with an integrated light quantity of 500 mJ / cm 2 The sample was irradiated with ultraviolet light. On the other hand, the above-mentioned hard coat composition (hard coat paint) was applied to the surface of the methacrylic resin layer of the above-mentioned base layer so that the dry coating thickness was 4 μm, and dried for 2 minutes at 100° C. At this stage, the hard coat composition was not cured. The two laminates were brought into contact with each other so that the coating surface of the low refractive index paint and the coating surface of the hard coat composition overlapped each other, and then pressed together at 60°C and 1.0 MPa to obtain a laminate for an anti-reflection film, which was then molded using a pressure molding machine. 2 The laminate was cured at 40° C. to obtain an anti-reflection film.
[0144] Next, comparative examples will be described. In the following comparative examples 1 and 2, the timing of curing the hard coat composition and molding the laminate is different from that of the above-mentioned example 1. [Comparative Example 1] The above-mentioned low refractive index paint was applied to the release surface of a 50 μm-thick release PET film (TR manufactured by Nippa Corporation) to a dry coating thickness of 100 nm, and dried at 100° C. for 2 minutes. Then, using an ultraviolet curing device, the dry coating side of the release PET film was exposed to an integrated light dose of 500 mJ / cm 2 The sample was irradiated with ultraviolet light. On the other hand, the above-mentioned hard coat composition (hard coat paint) was applied to the surface of the methacrylic resin layer of the above-mentioned base layer so that the dry coating thickness was 4 μm, and dried for 2 minutes at 100° C. At this stage, the hard coat composition was not cured. The two laminates were brought into contact with each other so that the coating surface of the low refractive index paint and the coating film of the hard coat composition overlapped each other, and then pressed together at 60°C and 1.0 MPa to obtain a laminate for an anti-reflection film. The laminate was then cured with an ultraviolet curing device at an integrated light dose of 1000 mJ / cm. 2The thus-obtained anti-reflective film was molded using a pressure molding machine.
[0145] [Comparative Example 2] The above-mentioned hard coat composition (hard coat paint) was applied onto the surface of the methacrylic resin layer of the above-mentioned base material layer so that the dry coating thickness was 4 μm, and then dried at 100° C. for 2 minutes. Further, the hard coat composition was cured with an ultraviolet curing device at an integrated light dose of 500 mJ / cm 2 . 2 The coating film side of the hard coat composition was irradiated with ultraviolet light at 100° C. At this stage, the hard coat composition was cured. Furthermore, the above-mentioned low refractive index paint was applied onto the coating of the hard coat composition so that the dry coating thickness was 100 nm, and then dried at 100°C for 2 minutes. Furthermore, using an ultraviolet curing device, it was cured with an integrated light dose of 500 mJ / cm. 2 The coating side of the low refractive index paint was irradiated with ultraviolet light at 1000 nm to obtain an anti-reflection film. At this stage, the coating film of the low refractive index paint was cured. The anti-reflection film thus obtained was molded using a pressure molding machine.
[0146] The physical properties of the laminates for antireflection films and antireflection films thus produced in each of the Examples and Comparative Examples were measured as follows. <Physical property measurements> Adhesion: The release PET film was removed from the cured coating of the anti-reflective film, and 11 cuts were made vertically and horizontally at 1 mm intervals with a cutter to create 100 grids. Cellotape (registered trademark) (adhesive tape made by Nichiban Co., Ltd.) was attached to these grids and then peeled off in a 90° direction in one go. The number of grids that remained without the cured coating peeling off was counted. The state in which the coating was still present in all grids was evaluated as "good", and the state in which even a small amount of peeling off was evaluated as "poor".
[0147] Pencil hardness: The pencil hardness of the surface of the anti-reflection film on the side of the low refractive index coating was evaluated after removing the release PET film. Measurements were performed based on the conditions of JIS K-5400, and the hardest pencil that did not cause scratches was used to evaluate the hardness. Scratch resistance: After removing the release PET film, apply 100gf / cm2 #0000 steel wool to the surface of the low refractive index paint side of the anti-reflective film. 2 The sample was scratched by moving it back and forth 15 times under a pressure of 1.0 mm. Based on JIS K 7136:2000, the absolute value of the haze change (ΔH), which is the difference between the haze value measured before the scratch test and the haze value measured after the scratch test based on JIS K 7136:2000, was calculated and evaluated. For the examples and comparative examples in which the ΔH value was less than 2.0%, the scratch resistance was evaluated as good.
[0148] Refractive Index: In accordance with JIS K0062-1992, the refractive index (nD) was measured at 25° C. using an Abbe refractometer (model: NAR-1T LIQUID) manufactured by Atago Co., Ltd., with D-line at a wavelength of 589 nm. For solutions containing a solvent, the refractive index was measured while the solvent was still present, and the refractive index of the solution without the solvent was calculated from the measured value and the dilution rate of the solvent.
[0149] Reflectance (luminous reflectance): The reflectance of the surface of the low refractive index coating of the anti-reflection film from which the release PET film was removed was measured. Measurements were performed according to JIS Z 8722-2009 using SD6000 manufactured by Nippon Denshoku Industries Co., Ltd. In order to prevent reflection from the back surface (substrate layer side) of the film in each example, black vinyl tape was attached to the surface opposite the coating surface.
[0150] Chemical Resistance: After removing the release PET film, Neutrogena SPF100 was applied to the surface of the anti-reflective film on the side of the low refractive index paint, and after leaving it at 80°C for 1 hour, the appearance was visually observed.
[0151] Thermoformability (including deep drawability and right-angle formability): The laminate for an antireflection film or the antireflection film obtained in each Example and Comparative Example was cut to 210 mm x 297 mm, and the polycarbonate resin side of the obtained sample was preheated at 190° C. for about 40 seconds. Then, the sample was placed in a mold including a right-angled protrusion having a deep drawing height of 13 mm and a length and width of 30 mm so that the base layer of the sample was in contact with the mold, and the laminate sample was subjected to pressure molding using high-pressure air of 1.5 MPa. In the thus obtained pressure-molded body, the radius R of the area in contact with the right-angled portion of the mold was within 3 mm and no cracks occurred in the coating layer on the pressure-molded body, and the comparative examples were evaluated as having good moldability. The radius R of the right-angled portion was actually measured using a contact-type contour measuring instrument CONTOURECORD2700 / 503 (manufactured by Tokyo Seimitsu Co., Ltd.).
[0152] The above-mentioned pressure molding method is as follows. First, the above-mentioned sample of the laminate for anti-reflection film or the anti-reflection film is fixed with a holder, and the sample is moved together with the holder to a heating zone, irradiated with infrared rays from above, heated to a temperature higher than the Tg of the sample sheet, and softened. Furthermore, the sample sheet is moved together with the holder onto a mold, clamped, and pressurized air is introduced at the same time. Then, the sample sheet is rapidly stretched until it contacts the mold surface, and then it is brought into contact with the mold surface and quenched to a temperature below the Tg of the sample sheet resin, thereby obtaining a shaped product fixed along the surface shape of the mold. After discharging the pressurized air, the shaped product is taken out, and the value of the radius R of the right-angled part is measured by the above-mentioned method.
[0153] The measurement results of the properties of each of the above-mentioned Examples and Comparative Examples are shown in Table 2. The refractive index in the table is the value of the paint before polymerization, and the refractive index value after polymerization was generally about 0.02 higher than the value of the paint before polymerization in each layer. [Table 2]
[0154] From the above, it was confirmed that, although the laminates for anti-reflection films of the Examples have excellent thermoformability, the anti-reflection films after curing have high interlayer adhesion, good scratch resistance, high surface hardness, excellent chemical resistance, and low surface reflectance. [Explanation of symbols]
[0155] 10 Laminate (second laminate) 12 First base material layer (base material layer: methacrylic resin layer) 14 Second base material layer (base material layer: polycarbonate resin layer) 16 Base film 16A Release surface 20 Uncured hard coat layer 40 Laminate (first laminate)
Claims
1. A base film having a release surface; an optical interference layer laminated on the release surface; an uncured hard coat layer having a curable hard coat composition and laminated on the optical interference layer on the side opposite to the substrate film; a substrate layer laminated on the uncured hard coat layer, the substrate layer including a polycarbonate resin; having The hard coat composition comprises a urethane acrylate oligomer; Laminate for anti-reflective film.
2. 2. The laminate for an anti-reflection film according to claim 1, wherein the optical interference layer and the uncured hard coat layer are pressure-bonded to each other so as to be in contact with each other.
3. 10. The laminate for an anti-reflective film according to claim 1, further comprising an adhesive layer laminated between the optical interference layer and the uncured hard coat layer.
4. 4. The laminate for an anti-reflective film according to claim 3, wherein the uncured hard coat layer comprises a curable, tack-free hard coat composition.
5. The refractive index of the base layer is 1.49 to 1.65, and the difference between the refractive index of the base layer and the refractive index of the uncured hard coat layer is 0.04 or less.
6. The optical interference layer has a low refractive index layer having a refractive index lower than that of the base layer or a high refractive index layer having a refractive index higher than that of the base layer.
7. 7. The laminate for an anti-reflection film according to claim 6, wherein the refractive index of the base layer is 1.49 to 1.65, and the refractive index of the low refractive index layer is 1.31 to 1.
41.
8. 8. The laminate for an anti-reflection film according to claim 6, wherein the refractive index of the base layer is 1.49 to 1.65, and the refractive index of the high refractive index layer is 1.68 to 1.
75.
9. The optical interference layer has the low refractive index layer and the high refractive index layer, and the high refractive index layer is laminated between the base layer and the low refractive index layer.
10. The optical interference layer has only one layer of the low refractive index layer, or one layer of the high refractive index layer and one layer of the low refractive index layer are laminated together. The laminate for an anti-reflection film according to any one of claims 6 to 8.
11. 11. The laminate for an anti-reflection film according to claim 1, wherein the thickness of the base layer is 50 to 500 μm, and the thickness of the uncured hard coat layer is 1 to 10 μm.
12. 4. The laminate for an anti-reflection film according to claim 3, wherein the adhesive layer has a thickness of 1 to 10 μm.
13. 7. The laminate for anti-reflection films according to claim 6, wherein the low refractive index layer has a thickness of 10 to 200 nm.
14. 7. The laminate for anti-reflection films according to claim 6, wherein the high refractive index layer has a thickness of 10 to 300 nm.
15. 15. The laminate for an antireflection film according to claim 1, wherein the optical interference layer comprises a polymer of a resin material containing a urethane acrylate and a (meth)acrylate.
16. The laminate for an anti-reflection film according to claim 15 , wherein the resin material comprises a fluorine-containing urethane acrylate.
17. 4. The laminate for an anti-reflection film according to claim 3, wherein the adhesive layer comprises an oligomer and / or polymer having a urethane bond, which is a reaction product of an oligomer and / or polymer of an acrylate compound having at least one hydroxyl group and an isocyanate compound having at least one isocyanate group that bonds with the hydroxyl group to form a urethane bond.
18. 18. The laminate for an antireflection film according to claim 17, wherein the acrylate compound is an alkyl acrylate compound having 30 or less carbon atoms, and the isocyanate compound is an isocyanate compound having 20 or less carbon atoms and a methacryl group.
19. The laminate for an antireflection film according to claim 17 or 18, wherein the adhesive layer contains an oligomer and / or polymer having a urethane bond represented by the following formula (1): 【Chemistry 1】 (In formula (1), n is an integer from 1 to 20.)
20. The laminate for an antireflection film according to any one of claims 1 to 19, wherein the optical interference layer is of an ultraviolet-curable type.
21. 21. The laminate for anti-reflection films according to claim 1, wherein the base material layer of a sample of the laminate for anti-reflection films obtained by cutting into a size of 210 mm x 297 mm x 0.3 mm (thickness) is preheated at 190°C for 40 seconds, the sample is placed in a mold having a deep-drawing height of 13 mm and including a right-angled protrusion having a length and width of 30 mm so that the base material layer is in contact with the sample, and pressure molding of the sample of the laminate for anti-reflection films is performed using high-pressure air of 1.5 MPa, and the radius R of the region in contact with the right-angled protrusion of the mold obtained is 3.0 mm or less.
22. An antireflection film comprising the laminate for an antireflection film according to any one of claims 1 to 21.
23. the antireflection film has a cured hard coat layer formed by curing the uncured hard coat layer, The anti-reflection film according to claim 22, wherein the refractive index of the substrate layer is 1.49 to 1.65, and the difference between the refractive index of the substrate layer and the refractive index of the cured hard coat layer is in the range of 0.04 or less.
24. the optical interference layer has a low refractive index layer having a refractive index lower than that of the base layer, 24. The anti-reflection film according to claim 22, wherein the refractive index of the base layer is from 1.49 to 1.65, and the refractive index of the low refractive index layer is from 1.31 to 1.
41.
25. a first lamination step of laminating an optical interference layer on a release surface of a substrate film to form a first laminate; a second lamination step of laminating an uncured hard coat layer having a curable hard coat composition on one surface of the substrate layer containing a thermoplastic resin to form a second laminate; 2. The method for producing a laminate for an anti-reflection film according to claim 1, further comprising a third lamination step of pressing the first and second laminates together so that the optical interference layer of the first laminate and the uncured hard coat layer of the second laminate are in contact with each other.
26. An optical interference layer is laminated on the release surface of the substrate film; a first lamination step of laminating an adhesive layer on a surface of the optical interference layer opposite to the release surface to form a first laminate; a second lamination step of laminating an uncured hard coat layer having a curable, tack-free hard coat composition on one surface of the substrate layer containing a transparent resin to form a second laminate; 4. The method for producing a laminate for an anti-reflection film according to claim 3, further comprising a third lamination step of pressing the first and second laminates together so that the adhesive layer of the first laminate and the uncured hard coat layer of the second laminate are in contact with each other.
27. 27. The method for producing a laminate for an anti-reflection film according to claim 25 or 26, further comprising a first curing step of laminating a curable optical interference layer in the first lamination step and curing the optical interference layer between the first lamination step and the second lamination step.
28. The method for producing a laminate for an anti-reflection film according to any one of claims 25 to 27, further comprising a second curing step of curing the uncured hard coat layer after the third lamination step.
29. The method for producing a laminate for an antireflection film according to any one of claims 25 to 28, wherein a temperature during pressure bonding in the third lamination step is 20 to 100°C.
30. The method for producing a laminate for an antireflection film according to any one of claims 25 to 29, wherein in the third lamination step, a pressure of 4 MPa or less is applied to pressure-bond the first and second laminates.
Citation Information
Patent Citations
Hardening resin composition and Anti-reflection coating
JP2002145952A
Antireflection film, its manufacturing method and substrate
JP2004212619A
Antireflection transfer film and its manufacturing method
JP2007188045A
Active energy ray-curing adhesive
JP2011162770A
Laminated film for molding
JP2014041244A
